UFIDA (F) - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
In January 2010, UFIDA started its new three-year development plan. The goal was clear: scale revenue to become a World Top 10 management software and service provider and gain number one position in the e-business service market in China. Financing was seen an essential tool to achieve these goals. This text outlines the strategies employed by UFIDA to achieve these goals.